Learning animals : curriculum, pedagogy and becoming a veterinarian - Dolby, Nadine, 1964- (Boca Raton : CRC Press, 2022)
We are surrounded by thousands of animals, alive and dead. They are an intimate and ever-present part of our human lives. As a society, we privilege veterinarians as experts on these animals: they are our educators and teachers in what they say, what they do, and the decisions that they make. Yet, within the field of education, there is little research on the curriculum, pedagogy, and experiences of veterinary school and students. What do veterinarians learn in veterinary school? How do their experiences during those four years shape their perceptions of animals? How do the structures, curriculum, and pedagogy of veterinary college create and influence these experiences? Learning Animals opens up this conversation through an exploration of the complicated, fascinating and often painful stories of a cohort of veterinary students as they make their four-year journey from matriculation through graduation. The book examines how the experiences of veterinary students shape how humans relate to animals, from public policy and decision-making about the environment and animals slaughtered for food, to the most personal decisions about euthanizing companion animals. The first full-length, critical, qualitative study of the perspectives of our primary teachers about animals, this will be a thought-provoking read for those in the fields of both educational research and veterinary education.
Chapter 1. Introduction: Animals, Education and Change Chapter 2. Animals in Education: An OverviewChapter 3. Beginnings: Contexts, Memories, and Stories Chapter 4. Encountering Animal Bodies Chapter 5. Stepping Out: Learning in the WildChapter 6. Endings: There Are No Animals HereChapter 7. Telling New Stories: Towards Different Animal and Human FuturesChapter 8. Turning Stories into New Love: Possibilities Chapter 9. A Researcherś Tale: Making Change for Animals
OCLC-licensed vendor bibliographic record.
Keywords: Veterinary medicine -- Study and teaching; Veterinary students; Human-animal relationships; EDUCATION / Adult & Continuing Education; EDUCATION / Educational Psychology; EDUCATION / General